PENGARUH DOKTRIN HAKKO ICHIU TERHADAP PENERAPAN KEBIJAKAN JEPANG DI INDONESIA (1942-1945) - Hestiya; Clara Cynthia Putri Rahasri; Alif Nur Hafidz; Pratama, Kahfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the influence of the Hakko Ichiu doctrine on Japanese occupation policies in Indonesia during the period of 1942–1945. Hakko Ichiu, which literally means “eight corners of the world under one roof,” became the ideological foundation of the Japanese Empire’s expansion by positioning Japan as the leader of Asia that aimed to liberate Asian nations from Western imperialism. This research aims to analyze the implementation of the doctrine in the fields of education, mass media propaganda, and socio-political mobilization during the Japanese occupation in Indonesia. The study employed a historical research method using qualitative approaches through the analysis of Dutch newspaper archives, historical documents, and related literature. The findings reveal that the Hakko Ichiu doctrine was systematically implemented as an ideological instrument to legitimize Japanese domination in Indonesia. In practice, the doctrine created contradictions between the rhetoric of Asian brotherhood and the reality of exploitative and militaristic colonialism. Japanese propaganda successfully mobilized Indonesian society through organizations such as PETA, Seinendan, and Jawa Hokokai. However, the occupation also caused severe economic hardship, social suffering, and humanitarian crises among the Indonesian people. Therefore, the study concludes that Hakko Ichiu functioned not only as a political doctrine of Asian unity but also as a strategic tool to strengthen Japanese imperial interests in occupied territories.